ProTaper files in root canal preparation: Case report - Brkanić Tatjana (Serbian Medical Society - Dental Section, Belgrade, 2005)
The aim of this paper was to, on the basis of everyday clinical practice, show and analyse, the crown-down technique of root canal preparation with nickel-titanium rotary instruments. After the diagnosis of irreversible pulp disease on the second lower right molar, endodontic treatment was carried out. Root canal shaping was performed with modified crown-down technique with nickeltitanium rotary files (ProTaper, Meilffer), according to the manufacturer's recommendations. After root canal preparation, obturation was finished with AH26 and guttapercha points (.06 taper), using the lateral compaction technique.